Mathematical Problem-Solving Ability in STAD Learning Assisted by Question Cards in Terms of Student Learning Motivation - Mulyono; Amira Sulkha Fatika (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2024)
This research aims to determine the effectiveness of Student Teams Achievement Division (STAD) learning model assisted by question cards and description of mathematical problem solving ability in terms of students' learning motivation using STAD learning model assisted by question cards. The method used in this research is mixed method with sequential explanatory design. The subjects in this research were 6 people consisting of 2 students in each learning motivation category, namely high, moderate, and low. The results of this research showed that: (1) the mathematical problem-solving ability of grade VIII students after participating in STAD learning assisted by question cards on Probability material reaches learning completeness; (2) The average mathematical problem-solving ability of grade VIII students after participating in STAD learning assisted by question cards is higher than the average mathematical problem solving ability of grade VIII students who use conventional learning models; (3) The completeness of mathematical problem-solving ability of grade VIII students after participating in STAD learning assisted by question cards is more than the proportion of completeness of mathematical problem solving ability of grade VIII students using conventional learning models; (4) Subjects with high learning motivation fulfil all four indicators of mathematical problem-solving ability well. Subjects with moderate learning motivation fulfilled 3 indicators of mathematical problem-solving ability well.